2017
DOI: 10.1007/s00440-017-0777-x
|View full text |Cite
|
Sign up to set email alerts
|

Mass concentration and aging in the parabolic Anderson model with doubly-exponential tails

Abstract: ABSTRACT. We study the non-negative solution u = u(x, t) to the Cauchy problem for the parabolic equationHere ∆ is the discrete Laplacian on Z d and ξ = (ξ(z)) z∈Z d is an i.i.d. random field with doubly-exponential upper tails. We prove that, for large t and with large probability, most of the total mass U(t) := ∑ x u(x, t) of the solution resides in a bounded neighborhood of a site Z t that achieves an optimal compromise between the local Dirichlet eigenvalue of the Anderson Hamiltonian ∆ + ξ and the distanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(56 citation statements)
references
References 27 publications
0
56
0
Order By: Relevance
“…In [14] this was shown to also be the case for a model that replaced the Laplacian with the generator of a trapped random walk. By contrast, in very recent work [3] it has been shown that in the double-exponential case the PAM localises on a single connected island, rather than on a single site. This has confirmed the long standing conjecture that, in the i.i.d.…”
Section: Localisation In the Pammentioning
confidence: 81%
“…In [14] this was shown to also be the case for a model that replaced the Laplacian with the generator of a trapped random walk. By contrast, in very recent work [3] it has been shown that in the double-exponential case the PAM localises on a single connected island, rather than on a single site. This has confirmed the long standing conjecture that, in the i.i.d.…”
Section: Localisation In the Pammentioning
confidence: 81%
“…Similar results hold for a discrete relative of this operator, namely the Anderson model on ℓ 2 (Z d ), see e.g. [36,7,57,16,79,109]. The reason why these models are amenable to a very precise analysis is the applicability of Brownian motion, respectively random walk techniques and Feynman-Kac functionals.…”
Section: Lifshitz Asymptoticsmentioning
confidence: 52%
“…Now it is clear why the study of the Anderson Hamiltonian in [16] gave also results on the (adjacency) percolation Laplacian. Upper bounds on the IDS N BA λ imply upper estimates for the IDS of the adjacency and Dirichlet site percolation model.…”
Section: Percolation Hamiltonians On Cayley Graphsmentioning
confidence: 99%
See 2 more Smart Citations